Psychological aspects of hyperandrogenic states in late adolescent and young women. (6th May 2015) - Guidi, Jenny; Gambineri, Alessandra; Zanotti, Laura; Fanelli, Flaminia; Fava, Giovanni A.; Pasquali, Renato
Summary: Objective: The psychosocial implications of polycystic ovary syndrome (PCOS) phenotypes have been investigated in different patient populations, but little attention was paid to adolescent and young women. The aim of this study was to evaluate the psychosocial correlates of PCOS and other hyperandrogenic states in a population of late adolescent and young females and to provide a psychological characterization of specific clinical hyperandrogenic phenotypes. Design: This was a cross‐sectional study. Patients: High school female students, aged 16–19 years. Measurements: The study protocol was designed with three possible levels of participation characterized by an increased level of commitment. For the specific purposes of this investigation, we focused on the subsamples of students whose clinical state was assessed by medical examination ( n = 835) and for whom additional laboratory tests were available ( n = 394). Psychological evaluation encompassed psychological distress, levels of stress, well‐being, illness behaviour and quality of life (as measured by the Symptom Questionnaire, the Psychosocial Index and the Psychological Well‐Being scales ). Results: Significantly higher levels of psychological distress and impaired well‐being and quality of life were found among late adolescent and young women with isolated clinical hyperandrogenism compared to their normal counterparts. Furthermore, females with PCOS showed significantly greater hostility/irritability compared to healthy control subjects. Conclusions: These findings highlight the importance of early recognizing and adequately managing psychological distress in such patients.